Pengaruh Motivasi Kerja Terhadap Kinerja Guru Di SDN 187 Palembang - Noprian; Riri Hanifa (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to analyze the influence of work motivation (X) on teacher performance (Y) at 187 Palembang Elementary School. This research is quantitative and data collection techniques through distributing questionnaires to respondents to be answered. The sample used is a saturated sample where all members of the population are sampled, namely 42 teaching staff. The method of data analysis is simple regression analysis with the help of SPSS (Service Products and Service Solutions) version 24. The results of this study indicate that partially work motivation (X) has a positive and significant effect on teacher performance (Y) at 187 Palembang Elementary School.